Nickel-catalyzed direct alkynylation of C(sp2)-H bonds of amides: an “inverse sonogashira strategy” to ortho-alkynylbenzoic acids. just accepted - Landge, Vinod Gokulkrishna; Shewale, Chinmay H.; Jaiswal, Garima; Sahoo, Manoj Kumar; Midya, Siba Prasad; Balaraman, Ekambaram (Catalysis Science & Technology, 2016)
Nickel-catalyzed direct alkynylation of C(sp2)–H bonds of amides using commercially available, inexpensive 8-aminoquinoline as a removable bidentate directing group is described. The present ortho-alkynylation has a broad substrate scope, functional group tolerance and high regiocontrol, and can be scaled up. The efficiency and selectivity of this strategy provide sustainable routes to a diverse array of ortho-alkynylbenzoic acids under Ni(II)-catalyzed conditions.